Isu Identitas Etnis dan Agama Dalam Kontes Politik (Kasus Pemilihan Gubernur Sumatera Utara 2018) - Sri Devi Valentina Simamora Devi Valentina Simamora; Turnomo Rahardjo (Interaksi Online, 2019)
In the election of the Governor and Deputy Governor of North Sumatra in 2018, there was a campaign using identity politics. Identity issues are increasingly being used after a riot in the election of the Governor of DKI Jakarta in the previous year, where the Deputy Governor of DKI Jakarta who was nominating at that time was Djarot Syaiful Hidayat to re-run in North Sumatra. The issue of identity is widely discussed by the people of North Sumatra both directly and through social media. The purpose of this research is to find out the experience of the community involved in campaign activities and receive information from mass media and social media, know the experience of the community when conducting political discussions, and know the meaning of the community regarding issues of ethnic identity, religion, to black campaigns. In order to obtain data for this study, researchers used a type of qualitative research with an interpretive paradigm and a phenomenological approach using in-depth interviews or in-depth interviews. The subjects in this study were North Sumatra native voters aged 17 years and over or married who took part in the 2018 election for governor of North Sumatra. The results of this study indicate that informants who are the campaign teams or volunteers from both pairs of candidates are directly involved in the campaign of each pair of candidates who are promoted, and other informants who do not participate in the campaign, actively seeking information about the election of governors from the mass media, online media, and social media. During the campaign period, there was information that contained ethnic issues such as the "native son" issue, religious issues such as " invitation to choose the candidates for the governor of the faith", and black campaigns on online media, Instagram social media, and Whatsapp instant messaging. When accessing the media, there is information that can foster confidence and that does not foster confidence. Political discussions conducted by the community occur face to face or through social media Instagram and Whatsapp. In the process of political discussion there is an invitation to choose a candidate pair on the grounds of one tribe or one religion. When conducting a political discussion, there is information and invitations that can influence and which do not influence informants to choose a pair of candidate. The meaning of the informants carried out on campaigns that use ethnic issues, religion, and black campaigns, differ from one another based on previous experience, different educational backgrounds, ethnicities, and religions.